Antioxidant and antimicrobial activity of protein hydrolysate extracted from porcine liver - VERMA, AKHILESH K; CHATLI, MANISH KUMAR; KUMAR, PAVAN; MEHTA, NITIN (The Indian Journal of Animal Sciences, 2017)
Protein hydrolysates were extracted from porcine liver using commercial proteases viz. alcalase, trypsin and papain. Porcine liver revealed appreciable amounts of protein (20.62%). Enzymatic hydrolysis of porcine liver hydrolysate (PLH) resulted in 23.56, 26.82 and 19.12% of degree of hydrolysis, respectively. Antioxidant activity such as 2–2 diphenyl–1-picrylhydrazyl (DPPH) and 2, 2-azino-bis-3-ethyl-benzthiazoline-6-sulphonic acid (ABTS) and ferric ion reducing power (FRAP) radicals were determined for PLH. All PLH samples showed slight decrease in the pH during hydrolysis while, they scavenged 42.27, 57.49 and 40.32% of DPPH radicals, respectively at sixth hour of hydrolysis. Trypsin hydrolysed PLH exhibited highest ABTS radical scavenging activity (86.79%) than alcalase hydrolysed PLH (74.62%) and papain hydrolysed PLH (70.63%). FRAP of PLH samples were found to be 13.69, 14.92 and 12.65% for alcalase, trypsin and papain extracted PLH samples, respectively. PLH obtained from trypsin hydrolysis showed highest antimicrobial activity followed by papain and alcalase PLH, respectively. However, all PLH have the potential to be a protein rich ingredient for use in formulated meat products and possible help in reduction of oxidative and microbial deterioration.